Enviromental discourses: Analysis of ecological modernization in modern cities - Flor, Daniela (2017)
Ecological modernization is a paradigm and an environmental discourse, whichpromotes sustainable development of cities, it considers that economic growthand environmental protection are not opposed to each other, and it includesenvironmental protection in an existing social, economic and governmental structure (status quo). The goal of ecological modernization is the development of new technologies and systems to manage environmental impacts. The main advantages are higher involvement of society and the development of new practices as the Clean Development Mechanisms (CDM) or industrial ecology, which creates an economic and environmental win-win situation. However, this theory is accused of not considering the whole context of the problem and that it is too optimistic regarding the development of technologies and their adoption. Ecological modernization is an environmental discourse that has helped modern cities to adopt environmental practices; nevertheless, the solutions need to be holistic.